2009
DOI: 10.1016/j.gaceta.2008.02.003
|View full text |Cite
|
Sign up to set email alerts
|

La medida de la morbilidad atendida en una organización sanitaria integrada

Abstract: The CRG grouping system aids analysis at different levels for clinical administration. Due to its composition, this system allows better understanding of the use, costs and quality of the set of services received by a population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 8 publications
1
16
0
5
Order By: Relevance
“…The main features that define this information system are: (1) unique identification patient files for all encounters (primary care, specialized care, and inpatient services) and (2) Among the possible risk adjustment systems, in this article we use the Clinical Risk Groups (CRGs) (version 1.2B) which allows classifying individuals in mutually exclusive categories while preserving clinical significance, and taking into account co-morbidities and severity levels [15,17]. From the three different models provided by the CRG software, we use the concurrent model.…”
Section: Data Sourcesmentioning
confidence: 99%
“…The main features that define this information system are: (1) unique identification patient files for all encounters (primary care, specialized care, and inpatient services) and (2) Among the possible risk adjustment systems, in this article we use the Clinical Risk Groups (CRGs) (version 1.2B) which allows classifying individuals in mutually exclusive categories while preserving clinical significance, and taking into account co-morbidities and severity levels [15,17]. From the three different models provided by the CRG software, we use the concurrent model.…”
Section: Data Sourcesmentioning
confidence: 99%
“…This new model makes it necessary to identify the specific needs of target populations and, based on this, diversify the services provided to better meet the requirements of various population groups and even specific individuals [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Since 2001, SSIBE has focused a line of research and development on the analysis of morbidity and expenditure considering individuals. We have grouped patients on an ongoing basis by morbidity using Clinical Risk Groups (CRGs) and analysed the relationship of these groups with resource use; it was found that 1% of patients used 22% of the healthcare budget [1, 5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation for writing this article came up during the development of the research project published by Inoriza et al [14]. The aim of the original project was to classify a specific patient population according to morbidity using the Clinical Risk Groups (CRG) model proposed by Hughes et al [15], obtaining also their individual costs.…”
Section: Introductionmentioning
confidence: 99%